2014
DOI: 10.1111/bjet.12198
|View full text |Cite
|
Sign up to set email alerts
|

Scripting and monitoring meet each other: Aligning learning analytics and learning design to support teachers in orchestrating CSCL situations

Abstract: Abstract:From the conceptualization to the evaluation of Computer-Supported Collaborative Learning (CSCL) scenarios, teachers address multiple tasks, sometimes being overwhelmed on account of the required time and associated burden. To support teachers in this endeavour, we propose to connect the pedagogical decisions made at design time with the analysis of the participants' interactions. Thus, teachers would be provided with relevant and coarse-grained information that could help them manage their CSCL scena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
117
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 116 publications
(121 citation statements)
references
References 20 publications
1
117
0
3
Order By: Relevance
“…Wise et al [43] sums up a list of studies that "underscore the idea that the use of a combined approach of LD, teacher inquiry into student learning and LA can produce effective new pedagogies" [43]. Rodriguez et al [44] are trying to combine scripting and monitoring and vice versa. To take advantage of this potential, teachers and instructional designers need to keep LA in mind while designing learning activities and the LD together to select the most appropriate LA indicators for the dashboard solution [44].…”
Section: Aligning La and Ld In Framework And Dashboardsmentioning
confidence: 99%
“…Wise et al [43] sums up a list of studies that "underscore the idea that the use of a combined approach of LD, teacher inquiry into student learning and LA can produce effective new pedagogies" [43]. Rodriguez et al [44] are trying to combine scripting and monitoring and vice versa. To take advantage of this potential, teachers and instructional designers need to keep LA in mind while designing learning activities and the LD together to select the most appropriate LA indicators for the dashboard solution [44].…”
Section: Aligning La and Ld In Framework And Dashboardsmentioning
confidence: 99%
“…The proposal presented in the previous section was iteratively applied to seven learning scenarios in higher education (Rodríguez-Triana et al, 2015). In this paper, we focus on the last two of these scenarios, which were designed to evaluate the proposal in its final version.…”
Section: First Scenario: Higher Educationmentioning
confidence: 99%
“…This section offers an overview of the learning contexts as well as how the proposal was implemented throughout the learning scenario lifecycle. We will not describe the results related to the application of the learning analytics approach as such, which have been reported elsewhere (see Rodríguez-Triana et al, 2015). We will focus on illustrating those aspects of the cases that had an influence on the ethical issues described in Section 2.…”
Section: First Scenario: Higher Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a longitudinal study of 38 modules by Nguyen, Rienties, Toetenel, Ferguson and Whitelock [29] indicated that by controlling for the heterogeneity between modules and time periods, LD could explain up to 69% of the variance in the time spent on VLE. In addition, Rodríguez-Triana, Martínez-Monés, Asensio-Pérez and Dimitriadis [34] illustrated the potential of orchestrating a monitoring-aware design process, and scripting-aware monitoring process to support instructors to design computer-supported collaborative learning activities. The consideration of instructional condition is crucial for the development of LA, as it could prevent over-or underestimation of the effect of behaviour in VLE on performance [12].…”
Section: Introductionmentioning
confidence: 99%